Socio‐Occupational Integration of Chinese Migrant Women in Andalusia Through Spanish Language Training - Esther Cores-Bilbao; Mariló Camacho-Díaz (Social Inclusion, 2023)
The present article explores the perceived role of work and proficiency in a second or additional language(s) among a group of Chinese migrant women learning Spanish in Andalusia. The enrolment of Chinese adult learners in language upgrading programmes in immersion contexts is relatively low, as Chinese expatriates tend to establish close‐knit, socio‐culturally elusive communities whose interactions with local residents are often limited to work‐related purposes. The distinctiveness of this ethnographic work lies in its focus on women who, having resided in southern Spain for extended periods and aiming to emancipate themselves from male family referents, have only recently sought greater inclusion in Spanish society. Through in‐depth interviews, these women’s prospects for professional advancement and self‐employment are also identified, albeit subsidiarily, among the reasons for pursuing higher levels of linguistic competence. The results point to a desire to develop higher levels of competence in linguistic, civic, and socio‐cultural literacies to expand their social networks and engage more actively in the communities where they currently live. Avoiding vulnerability to potential deception in the workplace and administrative settings, coupled with the need to participate in better‐informed decision‐making at the personal level, is also highlighted as contributory factors to their willingness to pursue multiliteracies in linguistic, civic, and occupational areas. The conclusions point to a mismatch between the training aspirations of these women and the curricula of the courses available to them within a Chinese educational organisation, whose focus lies almost entirely on the development and reinforcement of linguistic skills.